Vision-based body tracking: turning Kinect into a clinical tool - Morrison, Cecily; Culmer, Peter; Mentis, Helena; Pincus, Tamar (Disability and Rehabilitation: Assistive Technology, 2014)
Purpose: Vision-based body tracking technologies, originally developed for the consumer gaming market, are being repurposed to form the core of a range of innovative healthcare applications in the clinical assessment and rehabilitation of movement ability. Vision-based body tracking has substantial potential, but there are technical limitations. Method: We use our “stories from the field” to articulate the challenges and offer examples of how these can be overcome. Results: We illustrate that: (1) substantial effort is needed to determine the measures and feedback vision-based body tracking should provide, accounting for the practicalities of the technology (e.g. range) as well as new environments (e.g. home). (2) Practical considerations are important when planning data capture so that data is analysable, whether finding ways to support a patient or ensuring everyone does the exercise in the same manner. (3) Home is a place of opportunity for vision-based body tracking, but what we do now in the clinic (e.g. balance tests) or in the home (e.g. play games) will require modifications to achieve capturable, clinically relevant measures. Conclusions: This article articulates how vision-based body tracking works and when it does not to continue to inspire our clinical colleagues to imagine new applications.